2005
DOI: 10.1080/13548500512331315398
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation: The psychological changes that predict health outcome and healthy behaviour

Abstract: Although there is good evidence that cardiac rehabilitation is effective in improving health outcomes, little is known about the psychological changes that may contribute to these outcomes. This study describes changes in cognition, emotion, behaviour, and health following cardiac rehabilitation and investigates predictors of health outcome and healthy behaviour. Sixty-two people were followed up 2 months after the end of a cardiac rehabilitation programme and 29 people were followed up for 8 months. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
2
26
1
1
Order By: Relevance
“…In contrast, the patients who deemed the physiological and psychological risk factors the reason behind their cardiac condition felt that they had no control over their present conditions and, therefore, suffered from higher anxiety levels. Accordingly, based on the theory of Michie et al (2005), higher anxiety among our cardiac patients can be predicted by their perceived lack of control over their illness (15). The other findings of the current study indicated no significant difference between the patients who related their cardiac condition to the biological or environmental factors and those who recognized the behavioral, physiological, and psychological factors as the cause of their disease.…”
Section: Discussionsupporting
confidence: 37%
See 1 more Smart Citation
“…In contrast, the patients who deemed the physiological and psychological risk factors the reason behind their cardiac condition felt that they had no control over their present conditions and, therefore, suffered from higher anxiety levels. Accordingly, based on the theory of Michie et al (2005), higher anxiety among our cardiac patients can be predicted by their perceived lack of control over their illness (15). The other findings of the current study indicated no significant difference between the patients who related their cardiac condition to the biological or environmental factors and those who recognized the behavioral, physiological, and psychological factors as the cause of their disease.…”
Section: Discussionsupporting
confidence: 37%
“…The results demonstrated that those who regarded physiological and psychological factors as the cause of their disease showed more anxiety than those who considered behavioral factors as the reason for their disease. This finding can be clarified by a theory proposed by Michie et al (2005), who argued that in patients with MI, increased perceived control over the cardiac condition decreases anxiety and depression (15). Along the same lines, among our study population, it seems that the individuals who identified the behavioral risk factors such as unhealthy diet and physical inactivity as the underlying cause of their cardiac condition were no longer worried about the possible negative effects of these risk factors because they attributed their disease to one of these risk factors and, thus, sought to control them by improving their personal behaviors such as having a good diet and physical activity through rehabilitation programs.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, even when cardiac rehabilitation is successful, the psychological mechanisms underlying positive health change are poorly understood [37]. Individuals who feel that their lives are meaningful and fulfilling may be motivated to comply with physicians' advice to engage in positive health behaviors [10,19].…”
Section: Discussionmentioning
confidence: 99%
“…This is a worrying finding that indicates loss of benefits gained from rehabilitation (in women, a similar effect was seen for the emotional QoL dimension). These benefits include the ability to control disease, reduction in anxiety and depression, and increased self-competence regarding modification of health-related behaviours [15]. Perhaps with good functioning of men, the therapeutic team is not alert enough and believes that the treatment goes well and prognosis is good.…”
Section: Discussionmentioning
confidence: 99%